Circulating Follicular Helper–Like T Cells in Systemic Lupus Erythematosus: Association With Disease Activity. Issue 4 (April 2015) - Choi, Jin‐Young; Ho, John Hsi‐en; Pasoto, Sandra G.; Bunin, Viviane; Kim, Sang Taek; Carrasco, Solange; Borba, Eduardo F.; Gonçalves, Celio R.; Costa, Priscila R.; Kallas, Esper G.; Bonfa, Eloisa; Craft, Joseph
Abstract : Objective: To assess circulating follicular helper T (Tfh)–like CD4+ T cells in patients with systemic lupus erythematosus (SLE) and determine their relationship to disease activity. Methods: Blood samples from patients with SLE, as well as blood samples from patients with Behçet's disease (BD) and healthy individuals as controls, were analyzed. In all samples, circulating Tfh‐like cells were enumerated by flow cytometry, using, as markers, expression of CXCR5, inducible T cell costimulator (ICOS), and programmed death 1 (PD‐1) protein, as well as secretion of interleukin‐21 (IL‐21). The frequency of circulating Tfh‐like cells was compared to that of circulating plasmablasts (CD19+IgD−CD38+). In addition, the possible association of circulating Tfh‐like cells with the SLE Disease Activity Index (SLEDAI) was evaluated. Results: The subset of circulating Tfh‐like T cells, identified as CXCR5 high ICOS high PD‐1 high, was expanded in the blood of SLE patients compared to controls. Circulating Tfh‐like cells were found to produce IL‐21 and had lower expression of CCR7 as compared to that in circulating CXCR5 high central memory T cells, thereby enabling their distinction. Expression of PD‐1, but not ICOS or CXCR5, was significantly elevated in circulating Tfh‐like cells from SLE patients compared to controls. PD‐1 expression among CXCR5 high circulating Tfh‐like cells correlated with the SLEDAI, frequency of circulating plasmablasts, and anti–double‐stranded DNA antibody positivity, but not with disease duration or past organ injury; rather, this cell profile appeared to be a reflection of current active disease. Conclusion: Circulating Tfh‐like cells are associated with disease activity in SLE, suggesting that their presence indicates abnormal homeostasis of T cell–B cell collaboration, with a causal relationship that is central to disease pathogenesis. These findings also suggest that circulating Tfh‐like cells provide a surrogate for aberrant germinal center activity in SLE, and that their PD‐1 expression offers a tool for measuring disease activity and monitoring the response to therapies.